PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN ANIMASI TERHADAP MINAT DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI KELAS X JURUSAN IPS SMA NEGERI 1 KUNDUR - Ramadhona, Selamat Febriadi; ', Caska; Trisnawati, Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research aims to know and analyze the influence of learning media animation of interest and the results of student learning Upper Secondary Schools (SMA) Land 1 Kundur, Karimun regency, Riau Islands Province. The place of this research carried out in the environment SMA Negeri 1 Kundur. This research started from February until March 2017. Now the type of this research is experimental studies, namely explain the research results in the form of data of interest and the results of student learning related to the learning media. The source of the data from this research is the data obtained from the value of the results of student learning and the value of questionnaires the perception of students toward the teacher can provide examples of media and an interest in learning. Now the data collection technique that is used by the method of ekperimen. The results of the study showed that learning media have a positive impact on the students learning results, but learning media does not affect the interest of student learning. This is due to less than optimal educators in the use of learning media.Key Words: Learning Media animation, interest learn, Learning Results